Ubiquitous flocculation activity and flocculation production basis of the conglutination mud from Ruditapes philippinarum along the coast of China - Jun Mu (Public Library of Science (PLoS), 2021)
Ruditapes philippinarum conglutination mud (RPM) is a typical waste by-product from manila clam R. philippinarum aquaculture. However, RPM from the clam at an aquaculture farm in Zhoushan, China, has been newly reported as a promising natural bioflocculant resource that contains effective flocculating polysaccharides from the clam associated bacteria. With an intent to figure out whether RPM flocculation activity is ubiquitous to the manila clam across a wide geographical range or only the Zhoushan location, and to explore the flocculation production basis and ultimately widen its exploitation scope, in this study, an extensive survey of RPMs from four representative locations along the coast of China was performed to determine their flocculation activity, polysaccharide constitution and bacterial community composition. Frozen preserved RPM samples from Zhoushan, Dalian, Weihai and Zhanjiang exhibited comparable flocculation activities (FRs) ranging from 61.9±2.4% to 73.2±0.9% at dosage of 8 g·L-1; while fresh RPMs from Zhoushan exhibited a much higher flocculation activity of 91.34±1.18% than its frozen counterpart. Polysaccharide extracts from the four locations showed similar monosaccharide constitutions to some extent. The geographical distribution led to certain variation in bacterial community structures. The similarity clustering of the polysaccharide compositions coincided with that of bacterial community structures from RPMs, suggesting that polysaccharides and respective bacterial communities might be the foundation of the flocculation activity for all RPMs. The overlapping OTUs across all the RPMs accounted for 44.6–62.22% of the overall sequences in each sample and contained the vast majority of the most abundant OTUs (Operational Taxonomic Units), forming a common "core microbiome" that is probably responsible for polysaccharide production and flocculation activity development.